2019
DOI: 10.1002/celc.201801731
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Fabricated Ni−P, Ni−S and Ni−Se Materials for Overall Water Splitting: Investigating the Concept of Bifunctional Electrocatalysis

Abstract: Transition‐metal‐based electrocatalysts containing chalcogenides (S and Se) or phosphorous have been extensively reported as bifunctional electrocatalysts for overall water splitting. However, there remains the question as to whether the pristine material is truly bifunctional with regards to inherent activity for both the hydrogen evolution reaction (HER) and the oxygen evolution (OER), which has implications for their use in commercial electrolyzers when coupled with renewable energy sources. Herein, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 70 publications
(72 reference statements)
3
43
0
Order By: Relevance
“…This study indicated that sulphur is removed from the catalyst material due to this oxidation process and was most likely the reason for the reduced HER performance after potential cycling. This conclusion was also consistent with previous work on electrochemically formed NiS x materials . This loss of sulphur was also seen with elemental mapping using SEM‐EDX on a larger scale (Figure S6) and therefore this phenomenon was prevalent across the entire sample.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This study indicated that sulphur is removed from the catalyst material due to this oxidation process and was most likely the reason for the reduced HER performance after potential cycling. This conclusion was also consistent with previous work on electrochemically formed NiS x materials . This loss of sulphur was also seen with elemental mapping using SEM‐EDX on a larger scale (Figure S6) and therefore this phenomenon was prevalent across the entire sample.…”
Section: Resultssupporting
confidence: 91%
“…The catalyst was also stable for the OER at a constant current of 10 mA cm −2 and the potential did not vary significantly over a period of 24 h (Figure S2b). There have been several reports relating to metal sulphide catalysts which demonstrated that the surface was in fact oxidised into metal oxide/oxyhydroxide species which were concluded to be the active form of the catalyst for the OER (accompanied by a reduction in the surface concentration of sulfur) . However, it has been postulated that the formation of −OOH intermediates from the coordinated OH groups on the surface of the catalyst can be encouraged by the delocalized electrons among the attached oxygen, metal centre, and the electronegative S atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated that the surface of metal sulphides is indeed oxidized to metal oxide/hydroxide, which were deduced to be the active species for OER, prior to OER along with sulphur depletion from the surface. [24,37,40] Consequently, the variation of the electrocatalytic activity with altered Fe : Ni ratio can be explained by the increased Ni 3 + active sites with the increase of the Ni content, considering Ni 3 + surface ions as the active sites in this pentlandite structure. Upon inclusion of more Fe into the structure, the amount of Ni 3 + on the surface is supressed and thus the activity is reduced.…”
Section: Electrocatalytic Oer Performancementioning
confidence: 96%
“…A typical pair of broad oxidation and reduction peaks is observable prior to the OER at about 1.45 and 1.35 V, respectively, which is attributed to Ni 2 + / Ni 3 + redox couple, agreeing with literature. [24,37] The oxidation peak is hypothesized to contribute into generating the active sites of the catalyst in Ni-containing catalysts. [38] Therefore, the intrinsic catalytic properties are presumably originated from the Ni ions on the metal chalcogenide surface.…”
Section: Electrocatalytic Oer Performancementioning
confidence: 99%